The Cloaked Intruder: An Unexpected Case of Eosinophilic Cholangitis. Issue 11 (November 2019) - Akolkar, Shalaka; Patel, Jalpa; Abdu, Backer; Sorser, Serge
Abstract : ABSTRACT: Often, when biliary strictures are evaluated, malignancy is high on the differential. However, it is important to consider benign and malignant causes because approximately 10% of biliary strictures are benign. Eosinophilic cholangitis is an extremely rare benign disorder of the biliary tract caused by fibrosis and stricture from eosinophilic infiltration. The etiology of the disease remains unclear, and often, patients present with obstructive jaundice. We present a young man who presented with obstructive jaundice and abdominal pain, with a biliary stricture and peripheral eosinophilia. The final surgical pathology revealed eosinophilic cholangitis.